Determinan Umat Nonmuslim dalam Menggunakan Jasa Bank Syariah - Muhammad Mashduqi; Ahmad Ramadhan (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
The development of Islamic banking in Indonesia has become a benchmark for the success of the existence of Islamic economics. Along with the development of the times, Islamic banks have many advantages because they are not only based on sharia so that transactions and activities become halal, but are open and do not specialize only for Muslim customers, but also for non-Muslims. Based on the results of the researcher's observations of several non-Muslim customers, the profit sharing profit sharing at the Rantauprapat sharia sub-branch of North Sumatra Bank is greater than that of conventional banks. As for the formulation of the problem in this study, is there any effect of service, profit, and promotion on the decisions of non-Muslims in using the services of Islamic banks. The purpose of this study was to determine the effect of service, profit, and promotion on non-Muslims' decisions to use Islamic bank services. The theory in this study is Islamic banking, Islamic banking products and services, factors that influence non-Muslims to use Islamic banking services which consist of service, profit and promotion. The approach in this research is a quantitative approach, the data source used is primary data. The data collection technique used was a questionnaire with a population of 3085 non-Muslim customers and a sample of 97 non-Muslim customers. Data processing uses the SPSS Version 26 application. The analysis technique used is validity test, reliability test, classic assumption test, normality test, multiple linear regression analysis test, hypothesis test. Based on the results of the t test that the service variable does not have a partial effect on the decision of non-Muslims to use the services of the North Sumatra bank Rantauprapat Sharia sub-branch. Meanwhile, the profit and promotion variables have a partial effect on the decision of non-Muslims to use the services of the North Sumatran bank, the rantauprapat sharia sub-branch. Based on the f test, it can be seen simultaneously that the service, profit and promotion variables have a significant influence on the non-seasonal decision to use the services of the North Sumatra bank branch of the Rantauprapat Sharia sub-branch.